Development of a code in python programming language to generate Ashby chart applied for materials selection (Innovation & Development in Engineering and Applied Science, 2020)
This study focuses on the development of a programming code to generate Ashby charts, which are used to optimize the mechanical design process in terms of reduction the materials selection time. The platform developed was carried out using python programming language and a database composed of 75 different types of materials that have been categorized in 7 regions (metals, ceramics, polymers, elastomer, natural, foams and composites) with their respective mechanical and thermal properties (Young's modulus, density, mechanical strength, thermal conductivity, thermal expansion and maximum service temperature). In order to perform the charts Ashby, the code first generates bubble diagrams in logarithm scale using the range of values of two desired properties, and then, these diagrams are grouped into regions through an envelope that is created using analytic geometry. For validation of the platform and the methodology, the obtained Ashby charts results were contrasted with charts provided by the CES Edupack 2017 software, from there the percentage of differences between the model developed and baseline charts were among of 2,8% to 15%. In consequence, the Ashby Charts obtained with the proposed code they are suitable for use in the selection of material.